The prevalence of different types of psychological dominant and psycho-emotional state in women with placental dysfunction - Yakymchuk, Nataliya (Psychosomatic Medicine and General Practice, 2019)
Placental dysfunction is a key problem in obstetrics, neonatology, pathology of the ante- and perinatal period, as the functional inability of placenta leads to an increase in the proportion of miscarriage, fetal development delay syndrome, or its antenatal death, and the period of pregnancy, especially in case of its pathological course, is an extremely strong psycho-emotional factor. The structure and prevalence of types of psychological component of gestational dominant with the consideration of psycho-emotional status in women with placental dysfunction were stated as well as their influence on reproductive loss and complication of pregnancy was estimated.